The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1245/s10434-013-3397-4
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of an R1 Resection in Gastric Cancer Patients Treated with Adjuvant Chemoradiotherapy

Abstract: A R1 resection was not an adverse prognostic factor in gastric cancer patients who had undergone CRT after the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 29 publications
0
22
0
4
Order By: Relevance
“…However, other randomised and non-randomised data suggest potential benefits from postoperative CRT even after optimal D2 dissection [I, B] [42][43][44][45], and this is the subject of ongoing randomised trials. Regarding patients who have had a microscopically incomplete resection, a retrospective comparison of the Dutch D1D2 trial has suggested significant improvements in OS and local recurrence rates with use of CRT after an R1 resection, a finding that has been confirmed by other retrospective series [IV, B] [41,46].…”
Section: Perioperative Chemotherapymentioning
confidence: 81%
“…However, other randomised and non-randomised data suggest potential benefits from postoperative CRT even after optimal D2 dissection [I, B] [42][43][44][45], and this is the subject of ongoing randomised trials. Regarding patients who have had a microscopically incomplete resection, a retrospective comparison of the Dutch D1D2 trial has suggested significant improvements in OS and local recurrence rates with use of CRT after an R1 resection, a finding that has been confirmed by other retrospective series [IV, B] [41,46].…”
Section: Perioperative Chemotherapymentioning
confidence: 81%
“…, was ebenfalls die genaue Indikationsstellung zur Nachresektion untermauert. Eine Reihe von retrospektiven Fallsammlungen weist unabhängig voneinander darauf hin, dass für Patienten mit R1-Situation eine postoperative Radiochemotherapie nicht nur die lokale Rückfallrate senkt, sondern auch das Überleben verbessert[509,510,515,516]. Patienten mit Adenokarzinom des Magens und des ösophagogastralen Übergangs mit primär nich resezierbaren Tumoren, lokalen Rückfällen oder makroskopischen Resttumoren nach inkompletter Resektion[517].…”
unclassified
“…This can be explained that patients undergoing total gastrectomy probably reflects larger tumors and unfavorable proximal lesions that prompt such a procedure. A positive resection margin was shown to be an independent adverse factor for survival in several surgical series before the advent of adjuvant CRT regarding patients who have had a microscopically incomplete resection, a retrospective comparison of the Dutch D1D2 trial has suggested significant improvements in OS and local recurrence rates with use of CRT after an R1 resection [29,30]. In our study, the surgical margin alter significantly outcome (Figure 4).…”
Section: Discussionmentioning
confidence: 48%